Risk of dysphagia in a population of infants born pre-term: characteristic risk factors in a tertiary NICU - Dwi Juliana Dewi; Elvie Zulka Kautzia Rachmawati; Luh Karunia Wahyuni; Wei-Chung Hsu; Susyana Tamin; Rahmanofa Yunizaf; Joedo Prihartono; R. Adhi Teguh Permana Iskandar (Elsevier, 2024)
Objective: To examine the prevalence and characteristics of dysphagia and suck-swallow-breath incoordination as phenotypes of oral feeding difficulties. Method: A cross-sectional study with secondary data collected consecutively over 2 years from October 2020 to October 2022 to measure the prevalence of swallowing and oral feeding difficulty in preterm infants using Flexible endoscopic evaluation of swallowing examination at the tertiary Integrated Dysphagia Clinic. Results: The prevalence of swallowing disorders was 25 % and the prevalence of suck-swallow-breath incoordination was 62.5 %. The significant risk factor that may show a possible correlation with oral feeding difficulty was mature post-menstrual age (p = 0.006) and longer length of stay (p = 0.004). The dominant percentage of upper airway abnormality and disorder were retropalatal collapse (40 %), laryngomalacia (42.5 %), paradoxical vocal cord movement (12.5 %), and gastroesophageal reflux disease (60 %). The dominant characteristic of oral motor examination and flexible endoscopic evaluation of swallowing examination was inadequate non-nutritive sucking (45 %), inadequate postural tone (35 %), and inadequate nutritive sucking (65 %). Conclusion: Dysphagia in preterm infants is mostly observed in those with mature post-menstrual age, longer length of stay, and the presence of gastroesophageal reflux disease with inadequate non-nutritive sucking and nutritive sucking abilities. Suck-swallow-breath incoordination is primarily observed in those with immature post-menstrual age, a higher prevalence of cardiopulmonary comorbidity, and a higher prevalence of upper airway pathologies (laryngomalacia, paradoxical vocal cord movement) with inadequate nutritive sucking ability.